THE RELATIONSHIP BETWEEN RESILIENCE AND WORK STRESS IN GENERATION Z RETAIL EMPLOYEES IN SURABAYA - Hanan, Maryam Alifah; Yuniasanti, Reny; Efendy , Mamang (Jurnal Konseling Pendidikan Islam, 2024)
The aim of this research is to determine the relationship between resilience and work stress among Generation Z retail employees in Surabaya. This research method is a correlational type of quantitative research whose data is in the form of quantitative data. The sampling technique used in this research was accidental sampling, with a sample size of 92 subjects determined by calculating Gpower. The scales used in this research are the work stress scale adapted from Lovibond and Lovibond with a reliability value of 0.915 and the resilience scale adapted from Connor and Davidson with a reliability value of 0.952. Data analysis used Product Moment parametric statistics with the help of IBM SPSS Statistics 23. The research results showed that there was no significant relationship between resilience and retail employee work stress, indicating that retail employee work stress was not influenced by resilience.